Taping insect pollinators for quality seed production in onion - Karuppaiah, V; Soumia, P S; Thangasamy, A; Singh, Major (Indian Horticulture, 2019)
Quality seed production in onion is mainly driven by insect pollinators and their foraging visits. Amount of forage visitation, time of visitation, type of visit and visiting insects determine quantity of pollination and efficiency. Under natural condition, bees are the major pollinating agents in onion. However, use of chemical pesticides against onion thrips, Thrips tabaci, less diversity in and around the area of field and man-made factor like urbanization could have negative impacts on insect pollinating service. Therefore, it is critical to adopt sustainable way of approach to retain and conserve the existing insect pollinators and their diversity in onion ecosystem.